First record of Noctitrella Gorochov from China, with description of a new species (Orthoptera: Gryllidae: Podoscirtinae) - Liu, Hao-Yu; Shi, Fu-Ming (Zootaxa, 2013)
The genus Noctitrella Gorochov, 1990 is recorded to China for the first time. A new species is described and illustrated, N. denticulata sp. nov. (CHINA: Yunnan). A key to and a distribution map of the known species of this genus in the world are presented.